New mechanism for the cosmological red-shift explaining: non-observation of dark energy, large-number- coincidence and the cosmic coincidence - Tank, Hasmukh K. (International Journal of Advanced Astronomy, 2015)
Accepting Einstein’s General Relativity Theory, that the changes in the gravitational field can propagate at the speed of light, it is proposed here that: before an electron in an atom emits a photon, the energy (h f0) of the photon was a part of total energy of the atom; contributing to establish the gravitational-field around the atom. As soon as an electron in that atom emits a photon of energy h f0, and the photon starts moving away from the atom, the gravitational-field around the atom partly reduces, proportional to the photon’s energy h f0, and this wave of ‘reduced gravitational field’ propagates radially-outwards at the speed of light. And a part of energy of the photon gets spent in “filling” the ‘gravitational potential-well’ produced by its energy, when it was a part of energy of the atom. From the derivation presented here we find that the energy spent by the photon to “fill” the ‘gravitational potential-well’, during its inter-galactic journey manifests as the ‘cosmological red-shift’. And the so called ‘total-mass-of-the-universe’’ and ‘radius-of-the-universe’’ are just mathematically-equivalent mass and distance arising while converting electrostatic potential-energy into gravitational potential-energy. This is the reason why we find the large-number-coincidence (LNC). And since there is no expansion of the universe, there is no ‘cosmic coincidence’, that why only in this epoch we find the ‘large-number-coincidence’!